Karakteristik Kimia Snack bar Anggur Laut dan Edamame dengan Variasi Penambahan Tepung Tempe dan Mocaf: Chemical Characteristics of Snack bar from Sea Grapes and Edamame with Variations of Tempeh and Mocaf Flou - TALITHA, ZADA AGNA; Wahyuningtyas, Amalia; Putri, Anita Nurani (Universitas Bumigora, 2025)
Snack bars are nutritious light snacks with the potential to function as supplemental food in preventing stunting, a persistent chronic nutritional issue in Indonesia. This study utilizes local ingredients, namely sea grapes (Caulerpa sp.), which are rich in minerals, and edamame (Glycine max), which is high in plant-based protein, as toppings. Additionally, tempeh flour and mocaf are used as binding agents and additional nutritional sources, with mocaf selected for its gluten-free properties. This research aims to analyze the effect of varying mocaf and tempeh flour proportions on the chemical characteristics (moisture content, ash, fat, protein, carbohydrates, andtotal energy) of sea grape and edamame snack bars. A Completely Randomized Design (CRD) with a single treatment factor the ratio variations of mocaf and tempeh flour (100:0, 60:40, 50:50, 40:60, 0:100) was employed, with two replications and duplicate analysis. The data were analyzed using ANOVA at a significance level of α < 5%, and if significant differences were found, they were further examined using Duncan’s Multiple Range Test (DMRT). The results indicated that the variation in tempeh flour and mocaf additions significantly affected the chemical properties of the snack bars, including moisture, ash, fat, protein, carbohydrates, and total energy.”The conclusion of this study is that the combination of these local ingredients can be used to produce nutritious snack bars with potential as a healthy food alternative for stunting prevention. This research is expected to contribute to the development of innovative snack foods aimed at preventing stunting.